Via which stages, community developer will lead community toward social change / Behzad Saheb Zadeh and Nobaya Ahmad - Behzad, Saheb Zadeh; Ahmad, Nobaya (2010)
Community development workers often act as a link between community and local government. The role of the community developer is not to do the work or control the social and economical project but to help all participants of the project take part in the process of development in community. The community developer focuses more on organizing the involvement and direction of community members and less on being the person who does the actual tasks. The main question of this paper is that how community developer will be able to mobilise people to affect change in their lives? In other words; who is the community developer? What is the role of community developer in the process of social change? This is theoretical research that method of collection of data is document method. The community development worker’s role is to work with particular communities in order to collectively bring about social change. Community development workers mobilise community members to empower them to identify their needs, plan what they want to achieve, organise themselves and take action to achieve to social change in theirs community.